Learning by doing and learning by thinking: an fMRI study of combining motor and mental training - Olsson, C-J; Jonsson, Bert; Nyberg, Lars (Frontiers in Human Neuroscience, 2008)
The current study investigated behavioral and neural effects of motor, mental, and combined motor and mental training on a finger tapping task. The motor or mental training groups trained on a finger-sequence for a total of 72 min over six weeks. The motor and mental training group received 72 min motor training and in addition 72 min mental training. Results showed that all groups increased their tapping performance significantly on the trained sequence. After training fMRI data was collected and indicated training specific increases in ventral pre-motor cortex following motor training, and in fusiform gyrus following mental training. Combined motor and mental training activated both the motor and the visual regions. In addition, motor and mental training showed a significant increase in tapping performance on an untrained sequence (transfer). FMRI scanning indicated that the transfer effect involved the cerebellum. Conclusions were that combined motor and mental training recruited both motor and visual systems, and that combined motor and mental training improves motor flexibility via connections from both motor and cognitive systems to the cerebellum.